EFEKTIVITAS KEPEMIMPINAN TRANSFORMASIONAL DALAM MENINGKATKAN DISIPLIN GURU DI SEKOLAH DASAR ISLAM - Ibrohim, Busthomi; Adhani, Lina; Basyar, Ali; Nurnaningsih (Jurnal Manajemen Pendidikan Islam Al-Munadzomah, 2026)
This study examines the effectiveness of principals’ transformational leadership in improving teacher discipline in an Islamic elementary school and identifies its dominant contributing factors. A qualitative case study approach was applied at SD Islam Darunnajah Jakarta. Data were collected through in-depth interviews, observations, and documentation involving the principal and five teachers. The findings indicate that transformational leadership enhances teacher discipline through four dimensions: idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. The most influential factors are the principal’s role modeling, a consistent reward and sanction system, professional development support, and open communication. This study extends the application of transformational leadership theory within Islamic educational settings by integrating Islamic values into leadership practices